Antibiotic Resistance: One Health One World Outlook - Aslam, Bilal; Khurshid, Mohsin; Arshad, Muhammad Imran; Muzammil, Saima; Rasool, Maria; Yasmeen, Nafeesa; Shah, Taif; Chaudhry, Tamoor Hamid; Rasool, Muhammad Hidayat; Shahid, Aqsa; Xueshan, Xia; Baloch, Zulqarnain (Frontiers in Cellular and Infection Microbiology, 2021)
Antibiotic resistance (ABR) is a growing public health concern worldwide, and it is now regarded as a critical One Health issue. One Health’s interconnected domains contribute to the emergence, evolution, and spread of antibiotic-resistant microorganisms on a local and global scale, which is a significant risk factor for global health. The persistence and spread of resistant microbial species, and the association of determinants at the human-animal-environment interface can alter microbial genomes, resulting in resistant superbugs in various niches. ABR is motivated by a well-established link between three domains: human, animal, and environmental health. As a result, addressing ABR through the One Health approach makes sense. Several countries have implemented national action plans based on the One Health approach to combat antibiotic-resistant microbes, following the Tripartite’s Commitment Food and Agriculture Organization (FAO)-World Organization for Animal Health (OIE)-World Health Organization (WHO) guidelines. The ABR has been identified as a global health concern, and efforts are being made to mitigate this global health threat. To summarize, global interdisciplinary and unified approaches based on One Health principles are required to limit the ABR dissemination cycle, raise awareness and education about antibiotic use, and promote policy, advocacy, and antimicrobial stewardship.